Application Of Promotion Mix At Ma Oteh Coffee Shop - Owen Owen; Hesniati Hesniati (ConCEPt - Conference on Community Engagement Project, 2023)
Practical work at Ma Oteh Coffee Shop is useful for overcoming the problems being faced by the shop in terms of increasingly fierce competition, this practical work focuses on how to market products so that they have a higher level of sales compared to competitors and also focuses on promotions that will used. The method used in this practical work is to interview the owner of Ma Oteh Coffee Shop to get information about the situation around the shop, followed by developing a system that will be implemented. The marketing and promotion carried out aims to disseminate information about the existence of Ma Oteh Coffee Shop. The results obtained from this practical work are registering the shop on Go-Food, registering on Google Maps, creating an Instagram social media account and carrying out promotions using the Instagram Advertisement feature, as well as printing a menu list that will be used by the shop.